Potential Hydroponics Systems for Seed Potato Production in Tropical Conditions - Factor, T. L.; Lima Junior, S.; Miranda Filho, H. S.; Araujo, J. A. C. de [UNESP]; Castilla, N.; VanKooten, O.; Sase, S.; Meneses, J. F.; Schnitzler, W. H.; VanOs, E. (Int Soc Horticultural Science, 2012)
In tropical conditions such as Brazil, depending on the local altitude, potatoes can be planted and harvested in every month of the year successively, which favors pest and disease incidence, especially aphids transmission viruses. Therefore, obtaining good yield depends on constant pest and disease control and quality potato seed acquisition. One of the main strategies to increase a healthier seed potato multiplication rate and production is the use of hydroponic systems, with or without substrates, in channels, pots or boxes. In 2005 and 2008, researches investigated several hydroponic systems with and without the use of substrates. In the hydroponic systems without substrate, the aeroponic system resulted in the highest multiplication rate, with 47 tubers plant(-1) compared to NFT and DFT, 35 and 37 tubers plant(-1), respectively. With the use of substrates, the pot system obtained better results, reaching 12 tubers plant(-1), followed by the capillary system and boxes, with 8 and 7 tubers plant(-1), respectively. Potato seed production was influenced by hydroponics systems. Among hydroponic systems with substrate, the pots were shown as the best option. However, higher yields were obtained in the hydroponics systems without substrate, with the aeroponic system that provided the best results.
Keywords: Solanum tuberosum; substrate; NFT; greenhouse; aeroponics; minitubers